Editorial - Mercer, Sarah; Ryan, Stephen (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2015)
This is the second of two special issues of Studies in Second Language Learning and Teaching emerging from the first Psychology in Language Learning (PLL) conference, which took place in May 2014 at the University of Graz, Austria. In the first special issue, we observed how much research into the psychology of language learning and teaching is expanding both thematically and methodologically. In this second special issue, we hone in on some of the core issues that we believe are likely to feature prominently on the future research agenda, namely, emotions, the self, and contexts.
Keywords: editorial